2023
DOI: 10.3390/su15118861
|View full text |Cite
|
Sign up to set email alerts
|

Implementing European Union Provisions and Enabling Frameworks for Renewable Energy Communities in Nine Countries: Progress, Delays, and Gaps

Abstract: With the Clean Energy for all Europeans legislative package, the European Union (EU) aimed to put consumers “at the heart” of EU energy policy. The recast of the Renewable Energy Directive (RED II) acknowledged the importance of energy communities for the energy transition and introduced new provisions for renewable energy communities (RECs), empowering them to participate in the energy market. This article analyses the progress of transposing and implementing key provisions of the RED II that apply to RECs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The nonlinear Kairat-II equation, which describes the evolution of u(x, t), is addressed analytically in this section [38][39][40][41]:…”
Section: Explanation Of New Extended Direct Algebraic Techniquementioning
confidence: 99%
“…The nonlinear Kairat-II equation, which describes the evolution of u(x, t), is addressed analytically in this section [38][39][40][41]:…”
Section: Explanation Of New Extended Direct Algebraic Techniquementioning
confidence: 99%
“…The authors have also identified the need for more research regarding the sizing of energy communities. There were also gaps in the EC's frameworks in different countries [34]. Regarding electric mobility, it was mentioned that there is a knowledge gap due to the lack of socio-economic assessment, macro-level assessment, and the lack of integrated modeling approaches [35].…”
Section: Research Gapsmentioning
confidence: 99%
“…In Germany, the implementation of guaranteed feed-in tariffs precipitated a wave of new initiatives after 2010, while Denmark's pioneering status from the 1990s was thwarted by a paradigm shift in its wind energy development (Gorroño-Albizu et al, 2019;Kirch Kirkegaard et al, 2023). We anticipate that data for recent years will show a continued increase in many countries, including Austria, Italy, Greece, and Spain, as the ongoing process of transposing EU EC directives into national legislation continues to dismantle barriers (Fina & Fechner, 2021;Krug et al, 2023). Conversely, our data confirm that numbers are still small in many Eastern European countries (Capellán-Pérez et al, 2020;Schwanitz et al, 2022).…”
Section: Contribution Of Inclusive Sustainable Settlements (Sdg 11)mentioning
confidence: 99%
“…This led to instances where anecdotal evidence had to be considered. Moreover, the topic under investigation is currently undergoing rapid development as EU Directives (EU Directive 2019/944, 2019and EU Directive 2018/2001, 2018 regulating legal forms and activities of citizen-led energy initiatives are being implemented (see Krug et al, 2023;Palm, 2021;Fina & Fechner, 2021; the transposition tracker offered by RESCOOP at https://www.rescoop. eu/transposition-tracker; and the EC's notification board at https:// energy.ec.europa.eu/news_en).…”
Section: Introductionmentioning
confidence: 99%